DEVELOPING DIGITAL PICTURE SERIES AS A MEDIA FOR TEACHING WRITING NARRATIVE TEXT FOR GRADE X STUDENTS OF SMK NEGERI 1 PATUMBAK - Yayuk Yulianti; Ade Aini Nuran (Universitas Negeri Medan, 2022)
The aim of this study was to develop teaching media in Writing Narrative Text for Grade XStudents of SMK Negeri 1 Patumbak. This study was conducted by using Research andDevelopment (R&D) design from Borg, Gall and Gall (2003) through six phases; gatheringinformation and data, analyzing the data, media design, validating to experts, revision, andfinal product. The subjects of the study were an English teacher and 30 Grade X Students ofSMK Negeri 1 Patumbak. The data were gathered by administering interview to the Englishteacher and questionnaire distributed to 30 respondents to get the students’ needs. The resultof interview and questionnaire prove that the students need teaching media which canmotivate the students in learning writing narrative text. The product has been validated by theexperts by using validation sheets with the score 87% to linguistics aspects, 83% to processaspects, 80% to product and content aspects and 83% to layout aspects. The final score of thefour aspects is 73% from expert 1 and 93% from expert 2 which are range of 83%. The mediahas been developed in accordance to the students needs.